ESTIMASI NILAI PENURUNAN KESEHATAN AKIBAT POLUSI GAS NOX DI UDARA DKI JAKARTA - Listyarini, Sri; Tarumingkeng, Rudy C; Fauzi, Akhmad; Hutagaol, Parulian (Jurnal Matematika Sains dan Teknologi, 2007)
The aim of this research is to estimate the value of health degradation caused by nitrogen oxide (NOx) gas as one of the air pollutions in Jakarta Province. The economic growth in urban area may affect lifestyle which will increase the energy demand. Fossil fuel as the main energy emitting some gases to the ambient, one of them is NOx gas.  In this research analysis of factors that influenced NOx ambient concentration is based on the socials, economics, and meteorological data from Indonesia Statistics Center (BPS) and Bureau of Meteorology and Geophysics (BMG). The prediction of the cost that has to be paid by the persons who are exposured by NOx gas and will get respiratory symptomps is done by developing the dynamic simulation model. The result of this research is by 2025 the Jakarta residences that will have respiratory symptomps caused by the NOx air pollution should pay about 1 trillion (1012) rupiahs. To reduce this pollutant it is recommended to develop public policies based on the economic and environmental concern.